Micrometer measurements of double stars - Zulević D.J.; Popović G.M.; Pavlović R. (Serbian Astronomical Journal, 2000)
A set of 71 measurements of double and multiple stars, carried out with the Large Zeiss Refractor 65/1055 cm of the Belgrade Observatory, is communicated. The bulk of these measurements, 41 in all, unpublished yet, is due to late D. Zulević.